2021
DOI: 10.1021/acs.jpcc.1c00370
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Induced Structural Changes in the Liquid GaInSn Eutectic Alloy

Abstract: The temperature-dependent structure and properties of a liquid GaInSn eutectic alloy have been investigated by using in situ high-energy X-ray diffraction, thermal expansion, and heat capacity measurements together with ab initio molecular dynamics simulations. It is found that below and above 550 K, the liquid exhibits differences in heat capacity, density, the first two peak positions of the structure factor and pair distribution function, partial coordination numbers, polyhedron connection, as well as Bader… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…Zhang et al. and Wang et al saw a similar behavior for the ternary alloy Galinstan (see Figure b), , which might be due to excess heat capacity. Especially, Wang et al.…”
Section: Electrical and Thermal Transport Propertiesmentioning
confidence: 56%
See 4 more Smart Citations
“…Zhang et al. and Wang et al saw a similar behavior for the ternary alloy Galinstan (see Figure b), , which might be due to excess heat capacity. Especially, Wang et al.…”
Section: Electrical and Thermal Transport Propertiesmentioning
confidence: 56%
“…Reduction in heat capacity was also found for pure gallium in the liquid state. 228 Zhang et al and Wang et al saw a similar behavior for the ternary alloy Galinstan (see Figure 12b), 151,233 which might be due to excess heat capacity. Especially, Wang et al observed an anomaly in the course of the heat capacity at around 530 °C, which was ascribed to a liquid-to-liquid crossover (LLC).…”
Section: X C Xcmentioning
confidence: 62%
See 3 more Smart Citations